Guest Perceptions of Service Quality at Hotel Satria Wisata Parepare - Ulfiyah Putri Adha Bachtiar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to analyze the service system implemented at Hotel Satria Wisata in Parepare City and to identify guests’ perceptions of the hotel’s service quality based on cognitive, affective, and conative aspects as well as the SERVQUAL dimensions of hospitality services. Methodology: This study employed a descriptive qualitative research design. Primary data were collected through interviews and observations involving the HRD manager, hotel staff, and hotel guests. Secondary data were obtained from journals, books, and previous studies related to hotel service quality and guest perception. Data analysis techniques included data collection, reduction, presentation, and verification using the SERVQUAL framework. Main Findings: The findings revealed that Hotel Satria Wisata implemented service standards based on the five SERVQUAL dimensions, including responsiveness, empathy, reliability, tangibles, and assurance. Guests generally perceived the hotel services positively, particularly regarding staff friendliness, efficient check-in processes, accurate information, and comfortable facilities. However, several weaknesses were identified, such as inadequate room cleanliness, aging facilities, and malfunctioning hot water systems that affected guest satisfaction. Novelty/Originality of this study: This study provides a comprehensive qualitative analysis of guest perceptions toward hotel services by integrating SERVQUAL dimensions with cognitive, affective, and conative perception aspects in the context of a local hotel in Parepare City. The research contributes new insights into how service systems and guest experiences influence hotel image, satisfaction, and recommendation intentions in the hospitality industry.